Reversible strain control of magnetic anisotropy in magnetoelectric heterostructures at room temperature - Staruch, Margo (Sci Rep, 2016)
The ability to tune both magnetic and electric properties in magnetoelectric (ME) composite heterostructures is crucial for multiple transduction applications including energy harvesting or magnetic field sensing, or other transduction devices. While large ME coupling achieved through interfacial strain-induced rotation of magnetic anisotropy in magnetostrictive/piezoelectric multiferroic heterostructures has been demonstrated, there are presently certain restrictions for achieving a full control of magnetism in an extensive operational dynamic range, limiting practical realization of this effect. Here, we demonstrate the possibility of generating substantial reversible anisotropy changes through induced interfacial strains driven by applied electric fields in magnetostrictive thin films deposited on (0 1 1)-oriented domain-engineered ternary relaxor ferroelectric single crystals with extended temperature and voltage ranges as compared to binary relaxors. We show, through a combination of angular magnetization and magneto-optical domain imaging measurements, that a 90° in-plane rotation of the magnetic anisotropy and propagation of magnetic domains with low applied electric fields under zero electric field bias are realized. To our knowledge, the present value attained for converse magnetoelectric coupling coefficient is the highest achieved in the linear piezoelectric regime and expected to be stable for a wide temperature range, thus representing a step towards practical ME transduction devices.